Noncooperative Game of Distributed Quadrotor UAVs With Multiple Constraints - Geng, Mei-Jie; Ding, Hua-Feng; Yao, Xiang-Yu; Liu, Wen-Jin; Hua, Menghu (IEEE transactions on aerospace and electronic systems, 2024)
This article studies the noncooperative game of distributed quadrotor unmanned aerial vehicles (UAVs) under task, communication, and physical constraints. Compared to existing works that primarily focus on the flight task of Nash equilibrium seeking without task constraints or only with equality constraints, this study considers a noncooperative game with inequality constraints. To enhance the privacy of quadrotor UAVs communications, Markov jump networks are introduced as communication constraints to increase the stochasticity of the distributed system and all agents can search the Nash equilibrium by sharing virtual information. Furthermore, an effective fault-tolerant algorithm is proposed to address physical constraints, enabling all quadrotor UAVs to reach the generalized Nash equilibrium states subject to actuator faults, uncertain dynamic parameters, and time-varying disturbances. Then, the asymptotic stability of the proposed algorithms is proved by the projected gradient descent methodology and Lyapunov techniques. Finally, some simulations are conducted to verify the effectiveness of the suggested algorithms.